The fall and holocaust of Andalusian Muslims (1490-1614 CE/896-1023AH) : lesson of history which always will be repeated if it is not learned or became neglected - Kopanski, Ataullah Bogdan (SEFSI, Pusat Islam, 2011)
The Holocaust of Muslims ofAI-Andalus is one of the darkest pages of history of thc Christian Europe and simultaneously one of the most tragic periods in the history of the Islamic West. This era of the planned, sustained and systematically executed policy of total eradication of Islam from the southwestern Europe was authorized by the "Renaissance" popes and the European Roman-Catholic monarchs after the surrender of the last Muslim state of Granada in 1492 CE/897AH